A New Technique for Simultaneous Load Current Sharing and Voltage Regulation in DC Microgrids - Setiawan, M.; Abu-Siada, Ahmed; Shahnia, F. (IEEE, 2017)
IEEE Regulating the output voltage of distributed generation units while maintaining proper power sharing among them is a challenging control issue in dc microgrids. This paper presents a new technique to regulate the voltage levels across the dc microgrid loads and achieve proper load current sharing among the distributed generation units without directly regulating their output voltages. To implement the proposed technique, a hybrid communication scheme comprising centralized scheme for load current sharing and decentralized scheme for load voltage regulation is proposed. The dynamic performance of the investigated dc microgrid is examined under different operating conditions through extensive digital computer simulation analyses in MATLAB. The simulation results reveal the effectiveness of the proposed technique under different operating and loading conditions including constant-impedance, power, and current loads, communication link failure, and plug-and-play feature of the distributed generation units.